Armed conflict injuries to the extremities a treatment manual - Lerner, A. (Alexander); Soudry, M. (Michael) (Heidelberg, Germany Springer Berlin, 2011)
Modern weapons and high-energy accidents inflict devastating damage to soft tissue and bone. As a result, both primary treatment and late limb reconstruction present a difficult surgical challenge. This book is designed to meet the continued need to re-learn the principles of treatment of complex war injuries to the extremities in order to minimize post-traumatic and post-treatment complications and to optimize functional recovery.  Most of the chapters in the book are based on the unique experience gained in the treatment of military personnel who have suffered modern combat trauma and civilian victims of terror attacks at a single, large level 1 trauma center. The remaining chapters present the experience of leading international authorities in the field of trauma and reconstructive surgery. A staged treatment protocol is presented, ranging from primary damage control, including the use of external fracture stabilization, through to definitive functional limb reconstruction by means of various internal and external fracture fixation methods.  The organization of medical aid, anesthesiology, diagnostic imaging, and infection prophylaxis also receive detailed attention.  The management of potential complications such as delayed unions, non-unions, and osteomyelitis is reviewed, and controversies in limb salvage are considered.  Primary and late limb amputations are fully discussed, and a special chapter is devoted to the challenging dilemma of limb salvage versus amputation in the treatment of limbs at risk.  This well-illustrated book will be of value both to beginners and to experts in the field of trauma, including orthopedic surgeons, plastic surgeons, vascular surgeons, and military medical person
Organization of Urgent Medical Aid, Including Mass Casualty and Triage -- Wound Ballistics and Tissue Damage -- Damage Control Orthopaedics -- Crush Injury of the Limbs and Acute Mechanical Muscle-Crush Compartment Syndrome -- Anesthesia and Intensive Care of the Patient with Severe Extremity Trauma -- Hemotransfusion in Combat Trauma -- Diagnostic Imaging in Combat Trauma -- Tissue Debridement -- Primary External Fixation -- Prevention of Infection and Antibiotic Use in the Management of Armed Conflict Injuries to the Extremities -- Vascular Trauma to the Limbs -- Peripheral Nerve Injury -- Tissue Coverage After War Trauma -- Definitive Bone Fixation and Reconstruction: Conversion from Temporary External Fixation to Internal Fixation Methods -- Definitive Skeletal Reconstruction: Conversion to the Ilizarov Method -- War Injuries of the Hand -- Foot Surgery in War Trauma -- Limb Salvage Versus Amputation: The Dilemma -- Amputation in Combat Trauma -- Delayed Union and Nonunions -- Osteomyelitis -- Chronic Pain Subsequent to Armed Conflict Injuries to the Extremities.
Keywords: War wounds -- Treatment -- Handbooks, manuals, etc; Extremities -- Wounds and injuries; Wounds and Injuries -- Treatment